Pengaruh Social Media Marketing terhadap Keputusan Pembelian di Venue Golden Sriwijaya Building Kota Palembang - Handika Fikri Pratama; Wisanggeni Agus Priyanto; Aprigo Aprigo (Politeknik Negeri Sriwijaya, 2022)
With the advancement of technology in the current era of social media becoming popular in the community, especially instagram applications, many companies use instagram as a means of berbinis because of the many features in it such as feedphoto, story, and various effects to beautify the photos of products to be marketed. Not only that instagram application is also very accessible with the development of the internet, everyone can easily access so that the wider the market that will reach to influence consumers to be interested in the products offered. The formulation of the problem in this study is whether social media marketing affects purchasing decisions. The method used in this study is quantitative method. The data source is primary data and secondary data. Data collection techniques consist of observations, interviews, and questionnaires. The population in this study was 1878 as a social media follower of Instagram. For the data analysis process using simple regression analysis, coefficient of determination and t test with social media marketing as variable X (independent) and purchasing decision as variable Y (dependent). Social media marketing has a significant influence on purchasing decisions. With the result that social media marketing to purchase decisions is 67.2% while the remaining 32.8% is influenced by other variables that were not studied in this study. The conclusions in this study show that social media marketing variables have a significant effect on purchasing decision variables.